The Differences in the Clinical Outcome Based on Nutritional Status in Patients with Acute Ischemic Stroke in Academic Hospital UGM - Astari, Farida Niken; Sulistyo, Okta Haksaica; Rosyida, Lisa; ANP, Aprillia Dewi; Putri, Larasati Eka (Academic Hospital Journal, 2022)
Background: The prevalence of stroke in Indonesia according to Basic Health Research (RISKESDAS) 20131 was 7%, increasing to 10.9% in the Basic Health Research (Riskesdas) 20182. Malnutrition is a kind of complication which stroke patients often experience. Complications that often arise in stroke patients are malnutrition. The impact of hospital malnutrition increases patients' length of stay and disease complications.Objective: To determine the differences in clinical outcomes and length of stay in patients with acute ischemic stroke based on nutritional status at Academic Hospital UGM.Research Methodology: The research used a retrospective cohort design with purposive sampling. All respondents were selected because they met the inclusion criteria. The respondents' data were taken from medical records of inpatients at the UGM Academic Hospital from January to December 2019. Data analysis was analyzed by using the Kruskal Wallis test because the data were not normally distributed.Results: The result showed that stroke was more common in men (54.3%) with an average age of 60-74 years (55.5%). After being hospitalized, most of the patients' condition was improved (89%) with a no-risk screening score (85.5%). The nutritional status in stroke patients is good (44.5%). The length of stay (LOS) of stroke patients mainly was 4-7 days (75.7%) with an average NIHSS score of 5-15 or moderate (47.4%). The statistical test showed a value of p <0.05 to assess the difference in clinical outcomes of LOS and NIHSS scores on nutritional status.Conclusion: There were differences in clinical outcomes in LOS and NIHSS scores based on the nutritional status of acute ischemic stroke patients. Patients with poor nutritional status had higher LOS and NIHSS scores, followed by normal nutritional status and overweight status. Keywords: Acute Ischemic Stroke, clinical outcome, nutritional status